Building a bi-directional promoter binary vector from the intergenic region of Arabidopsis thaliana cab1 and cab2 divergent genes useful for plant transformation - Tindamanyire, Jimmy M.; Townsley, Brad; Kiggundu, Andrew; Tushemereirwe, Wilberforce; Sinha, Neelima (African Journal of Biotechnology, 2013)
The ability to express genes in a controlled and limited domain is essential to succeed in targeted genetic modification. Having tools by which to rapidly and conveniently generate constructs which can be assayed in a diverse array of plant species expedites research and end-product development. Targeting specifically green plant tissues offers an opportunity to effect changes to diverse processes such as water use efficiency, photosynthesis, predation and nutrition. To facilitate the generation of transgenes to be expressed in this domain, we created a series of plasmids called p2CABA based on the Arabidopsis thaliana chlorophyll a/b gene promoter, a single natural bidirectional promoter that can drive and express two different genes at the same time. Studies we carried out showed reporter gene, GUS expressed in leaves and stems but not in the roots, as expected since this endogenous promoter controls the expression of two photosynthetic genes in A. thaliana. We, therefore, utilized the intergenic region between the A. thaliana cab1 and cab2 divergent genes to design and construct a bidirectional promoter vector containing two multiple cloning sites and a gateway recombination cassette. This in turn will help minimize gene silencing and achieve desirable expression pattern of transgenes, a critical issue in plant genetic engineering and in this report we show their use in Medicago and tomato.
Keywords: Arabidopsis cab genes; bidirectional promoters; gene expression